PENDAMPINGAN PENATAAN TAMAN JURUG GEDE SEBAGAI UPAYA PENINGKATAN DAYA TARIK WISATA - Widyasari, Titiek; Tania Edna Bhakty; Nizar Achmad (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Visits to Jurug Gedhe have experienced a decline in tourists, so it is necessary to carry out a program to increase tourist attractions. The development of Jurug Gedhe Park is an artificial tourist attraction aimed at increasing the number of visitors. Assisting in the arrangement of Jurug Gedhe Park involves creating an initial sketch design of the park. This design includes a beautiful, lush, and colorful flower garden as an Instagrammable photo spot. It will also feature gazebos and comfortable seating to ensure visitors feel at ease and enjoy their time. The park is designed on an area of about 23 by 19 meters, facing west on the side of the highway. In front of the park, there is a parking area and the Jurug Gedhe tourist ticket booth. The entrance to the park is located on the south side, while the exit is on the north side. The park is surrounded by beautiful views of teak trees and other exotic and beautiful plants. The choice of Bougainvillea plants is based on their suitability for the extremely dry soil conditions, especially during the dry season. Bougainvillea plants are relatively easy to maintain, and with proper care, they will provide a beautiful display of colorful and lush flowers. The stimulant funding from Janabadra University will be used for the initial preparations to realize Jurug Gedhe Park, including the submission of a PDAM (Public Water Utility) installation request.